A Plug Assembly Line: An Assessment of Workstation Design and Working Posture - Adi , Saptari; Seri Rahayu , Kamat; Wan Hasrul , Wan Mahmud; Isa, Halim (Elsevier Ltd., 2007)
In most industry, assembly line job environments such as workstation design and working posture are factors contribute to workers’ performance. Workstation design such as: standing or sitting, the use of tools such as jig and the height of working table are influencing worker’s productivity. Meanwhile, working posture such as: position of body: arm and wrist, neck, trunk and leg determine comfortability and safe posture while working. These aspects also play a significant role in productivity.